Micro-photoluminescence mapping of light emissions from aluminum-coated InGaN/GaN quantum wells. (15th April 2019) - Tateishi, Kazutaka; Wang, Pangpang; Ryuzaki, Sou; Funato, Mitsuru; Kawakami, Yoichi; Okamoto, Koichi; Tamada, Kaoru
Abstract: Micro-photoluminescence (PL) mapping was investigated for Al-coated InGaN/GaN quantum wells (QWs), which showed huge PL enhancement by the surface plasmon (SP) resonance. The obtained images show inhomogeneity at the micro-meter scale; in addition, the region with lower PL intensities tend to have a longer PL wavelength for bare QWs. This correlation changed with an Al coating, positive correlations were observed in an area with a relatively short peak wavelength with blue-shift. Conversely, negative correlations were observed at longer peak wavelengths. These results suggest that the quantum-confined Stark effect (QCSE) was screened by the enhanced electrical-field of the SP resonance.